The Impact of a Multimodal Sport Science-Based Prehabilitation Program on Clinical Outcomes in Abdominal Cancer Patients: A Cohort Study. - Wooten, Savannah V.; Wolf Jr., J. Stuart; Mendoza, Diana; Bartholomew, John B.; Stanforth, Philip R.; Stanforth, Dixie; Tanaka, Hirofumi; Fleming, R.Y. Declan (American Surgeon, 2022)
Background: The potential for prehabilitation programs to impact clinical outcomes is uncertain in abdominal cancer patients due to the short window of time to intervene and the weakened state of the patients. To improve the effectiveness of prehabilitation intervention, a multimodal sports science approach was implemented.Methods: Prior to cancer-related surgery, 21 patients participated in a 4-week exercise and nutrition prehabilitation program comprised of blood flow restriction exercise (BFR) and a sports nutrition supplement. Retrospective data of 71 abdominal cancer patients who underwent usual preoperative care was used as a comparator control group (CON). At 90 days post-surgery, clinical outcomes were quantified.Results: Prehabilitation was associated with a shorter length of hospital stay (P = .02) with 5.5 fewer days (4.7 ± 2.1 vs 10.2 ± 1.2 days in CON) and decreased incidence of any complications (P = .03). Prehabilitation was not related to incidence of serious complications (P = .17) or readmission rate (P = .59). The prehabilitation group recorded 58% more steps on day 5 after surgery (P = .043).Discussion: A 4-week home-based prehabilitation program composed of BFR training and sports nutrition supplementation was effective in reducing postoperative complications and length of hospital stay in older patients with abdominal cancer.ClinicalTrials.gov Identifier: NCT04073381.